PENGARUH SECTIO CAESAREA METODE ERACS TERHADAP MOBILISASI DINI PADA IBU POST PARTUM DI RSIA PERMATA HATI MATARAM - Fidiya Rizka; Eti Sumiati; Dian Yuliani; Wahyu Cahyono (LPPM STIKES Mataram, 2025)
Introduction: Sectio caesarean (C-section) is a surgical procedure in which the delivery of an infant occurs through an incision in the lower abdominal wall. According to WHO, the C-section rates have risen by 10–15% in recent years. Early mobilization is a key factor in the postoperative recovery process. Therefore, the choice of method to accelerate early mobilization for C-section deliveries using the Enhanced Recovery After Cesarean Surgery (ERACS) method is regardered as highly effective. Objective: This study aims to analyze the effect of the ERACS method for C- section deliveries on early mobilization of postpartum mothers. Method: This study employed a comparative study design with a cross-sectional approach. The population consisted of postpartum mothers who underwent C- sections at RSIA Permata Hati Mataram, with a sample of 64 respondents divided into two groups (ERACS and conventional groups). Data were collected using observation sheets and analyzed using the independent t-test. Results: The results showed that the average mobilization initiation time in the ERACS group was 8 hours, with all respondents (100%) mobilizing within 0–12 hours. In contrast, the conventional group showed an average mobilization initiation time of 16.14 hours, with only 2 respondents (6.3%) mobilizing within 0–12 hours, while 30 respondents (93.7%) began mobilizing at 13–24 hours. Statistical analysis revealed the pvalue of 0.000 (<0.05), indicating a significant effect of the ERACS method on early mobilization. Conclusion: The ERACS method for C-section deliveries has a significant effect on early mobilization in postpartum mothers.